(untitled) (Development Service Industry Management, 2024)
In the rapidly evolving world of digital technologies, the role of digital marketing in the business environment is becoming increasingly crucial for achieving success and competitiveness. The rapid growth of internet users, digitization, and the extensive possibilities of applying artificial intelligence pose new challenges and opportunities for both marketers and entrepreneurs. The article explores the latest trends in digital marketing and characterizes the development vectors and promotion strategies that ensure successful online business development in the era of digital technologies. The research is dedicated to analyzing current trends in digital marketing, identifying key development vectors in this segment, and examining modern promotion strategies for effective online business management. Specifically, the study covers a wide range of issues, including the expansion of the use of artificial intelligence and machine learning in the development and implementation of marketing strategies, the adaptation of video marketing and streaming platforms to the new conditions of a rapidly developing digitized society, as well as the introduction of interactive content formats. Global trends such as globalization and international expansion, the importance of mobile marketing and adaptation to the latest mobile technologies, and the use of personalization and data analysis for creating individual strategies are thoroughly examined. The role of blockchain technologies in ensuring security and transparency in digital marketing is also highlighted. A comprehensive view is provided on various approaches to promoting business online, including inbound marketing to attract the target audience, the use of social networks to increase influence, optimization of paid advertising campaigns, and the importance of analytics for continuous improvement of strategies and determining key performance indicators. The conclusion emphasizes the necessity of constantly upgrading marketing strategies due to the rapidly changing digital environment and identifies key aspects that can serve as a foundation for further research and practical application in the field of digital marketing.